Study Feasibility Analysis of Biodiesel Energy Processing Used Cooking Oil - Suwarno Suwarno; Rohana Rohana; Ihsanurrizqie Indra Siregar (Budapest International Research and Critics University, 2021)
In research on renewable power plants. Fuel from petroleum, if consumed continuously, will run out over time. Research on alternative fuels to replace petroleum-based fuels continues to be carried out, one of which is research on Biodiesel/Biosol. Biodiesel is a substitute for diesel fuel derived from vegetable raw materials. The advantage of biodiesel over diesel is that it is more environmentally friendly. Biodiesel has started to be produced and marketed in Indonesia. Used cooking oil is easy to obtain, therefore the production of biodiesel from used cooking oil can be carried out by small industries. The process of producing biodiesel from used cooking oil uses the transesterification method. This research is expected to provide benefits as a business opportunity for small industrial-scale biodiesel production, provide economic value to used cooking oil, overcome household and industrial waste disposal, provide input to the industry so that they can produce fuel independently, and provide input to local governments so that they can producing biodiesel so that it becomes an energy-independent area. The physical test results of biodiesel from used cooking oil showed a density of 0.8780 gr/ml, a viscosity of 6.118 mm 2/s, a flashpoint of 178 oC, a carbon residue of 0.0006 %Wt, an ash content of 0.0397% WT, and a gross heating value of 19400 BTU/lb. In general, biodiesel has physical properties similar to diesel so it can be used as a mixture of diesel or diesel fuel substitutes.